2022
DOI: 10.1097/hjh.0000000000003271
|View full text |Cite
|
Sign up to set email alerts
|

Skin capillary alterations in patients with acute SarsCoV2 infection

Abstract: Background: Acute SarsCov2 infection is associated with endothelial dysfunction and 'endothelitis', which might explain systemic microvascular impairment. The presence of endothelial damage may promote vasoconstriction with organ ischemia, inflammation, tissue oedema and a procoagulant state resulting in an increase in the incidence of cardiovascular and cerebrovascular events. Microvascular thrombosis has been demonstrated in postmortem autopsy of COVID-19 patients; however, few data are available about skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Sulli et al 21 found that even in people with severe COVID-19, antivirals and biologics (such as IL-6 receptor antagonists) have a protective effect on capillary density. As the time from a SARS-CoV-2positive RT-PCR test to NFC exceeded 10 weeks in both patients and HCs, the capillaroscopic changes shown to return three months after COVID-19 by Rosei et al 22 may be another factor contributing to the similarity of capillary findings among the study groups. Further studies are needed to determine the conditions under which COVID-19 induces capillary changes or whether the resulting changes are reduced.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Sulli et al 21 found that even in people with severe COVID-19, antivirals and biologics (such as IL-6 receptor antagonists) have a protective effect on capillary density. As the time from a SARS-CoV-2positive RT-PCR test to NFC exceeded 10 weeks in both patients and HCs, the capillaroscopic changes shown to return three months after COVID-19 by Rosei et al 22 may be another factor contributing to the similarity of capillary findings among the study groups. Further studies are needed to determine the conditions under which COVID-19 induces capillary changes or whether the resulting changes are reduced.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, Karahan et al 19 found that patients with COVID-19 had a lower capillary density than HCs, and those who died of COVID-19 had a lower capillary density than those who survived. In addition, the systemic vascular effects of the virus are evidenced by changes such as capillary thrombosis, microhemorrhages, and angiogenesis detected during COVID-19, which disappeared in controls 3 months after discharge 22 . In the present study, the NFC findings did not differ among the groups, except for capillary ramifications.…”
Section: Discussionmentioning
confidence: 99%
“…This may result in a state of endothelitis with microvascular inflammation and capillary thrombosis mediated by cytokine storm and macrophage activation syndrome. 3 Another additional proposed mechanism was the antibody-dependent enhancement (ADE), due to the presence of non-neutralizing virusspecific antibodies (NAb), capable to promote Fcγ-mediated virus entry into the host cells. 4 Herein we describe the histopathological features of CrTE.…”
Section: Telogen Effluvium In Sars-cov-2 Infection: Histological Aspectsmentioning
confidence: 99%
“…For instance, the shapes of the nailfold and labial mucosa capillaries change due to systemic scleroderma 3 5 and chronic smoking, 6 respectively. Recent studies have suggested that COVID-19 may also be detected based on the changes in capillaries 7 , 8 . In capillaroscopy images, only the capillaries containing red blood cells (RBCs) are visible.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that COVID-19 may also be detected based on the changes in capillaries. 7 , 8 In capillaroscopy images, only the capillaries containing red blood cells (RBCs) are visible. Accordingly, by regarding observable capillaries as “functioning” capillaries, the quantification of the functional capillary density (FCD) was proposed.…”
Section: Introductionmentioning
confidence: 99%